Forest Tree Mycorrhiza - Bakshi, B. K.; Kumar, Dinesh (Indian Forester, 1968)
In forest trees, most absorbing roots are invaded by specific non-pathogenic soil fungi forming composite structures called mycorrhizae. Physiologically, the mycorrhizae represent a case of symbiosis. These associations are broadly classified as ectotrophic, endotrophic and ectendotrophic. In forest trees, ectotrophic mycorrhizae occur in Pinus, Picea, Abies, Cedrus, Eucalyptus, Populus and Salix among others; whereas endotrophic mycorrhizae are recorded in Taxus, Podocarpus, Cupressus and Araucaria among others. Ectendotrophic type is found on beech, lodgepole pine and ponderosa pine. The fungal symbionts of ectotrophic type belong mostly to Basidiomycetes and that of endotrophic type to Phycomycetes. Most of these fungi are ecologically obligate parasites; probably, they cannot survive in soil in the absence of host roots. Mycorrhizal development is favoured under strong sunlight, adequate soil moisture, aerated and acid soils and low levels of soil fertility. Their development is retarded when conditions are otherwise.Mycorrhizae have been shown to be beneficial to tree growth as they are more efficient than non-mycorrhizal roots in absorbing minerals in short supply. In addition, they expose a much larger total absorbing surface. This makes their presence obligatory for growth and survival of forest trees, especially exotics, under certain conditions as shown from experiences of planting failures due to lack of mycorrhiza in many countries. With large scale introduction of exotics in India, mycorrhiza is likely to play a dominant role in their establishment. When plants fail to develop mycorrhiza naturally, it may be necessary to introduce mycorrhiza for success of the species.